Outcomes after surgery in patients with and without recent influenza: a nationwide population-based study - Lam, Fai; Liao, Chien-Chang; Chen, Ta-Liang; Huang, Yu-Min; Lee, Yuarn-Jang; Chiou, Hung-Yi (Frontiers in Medicine, 2023)
Background: The influence of recent influenza infection on perioperative outcomes is not completely understood. Method: Using Taiwan National Health Insurance Research Data from 2008 to 2013, we conducted a surgical cohort study, which included 20544 matched patients with a recent history of influenza and 10272 matched patients without. The main outcomes were postoperative complications and mortality. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) for the complications and for mortality in patients with a history of influenza within 1-14 days or 15-30 days compared with non-influenza controls. Results: Compared with patients had no influenza, patients with influenza within preoperative days 1-7 had increased risks of postoperative pneumonia (OR 2.22, 95% CI 1.81-2.73), septicemia (OR 1.98, 95% CI 1.70-2.31), acute renal failure (OR 2.10, 95% CI 1.47-3.00), and urinary tract infection (OR 1.45, 95% CI 1.23-1.70). An increased risk of intensive care admission, prolonged length of stay, and higher medical expenditures was noted in patients with history of influenza within 1-14 days. Conclusion: We found that there was an association between influenza within 14 days preoperatively and the increased risk of postoperative complications, particularly the occurrence of influenza within 7 days prior to surgery.